2013
DOI: 10.1002/eji.201243185
|View full text |Cite
|
Sign up to set email alerts
|

Invariant natural killer T (iNKT) cell exhaustion in sarcoidosis

Abstract: Summary Invariant natural killer T (iNKT) cells are integral components of immune responses during many chronic diseases, yet their surface phenotypes, subset distribution, and polyfunctional capacity in this environment are largely unknown. Therefore, using flow cytometry, we determined iNKT phenotypic and functional characteristics in subjects with the chronic inflammatory disease sarcoidosis and matched controls. We found that sarcoidosis subjects displayed lower iNKT frequencies, which correlated with lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…We have shown that sarcoidosis CD4 + T cells derived from the periphery exhibit immune dysfunction when compared to healthy control cells (Figures 1 – 4 ). Together, these data reveal that the phenotypes observed in the periphery also occur at the site of local inflammation in the lung, a phenomenon also observed in sarcoidosis innate immune cells [ 33 ]. Thus, multiple immune defects characteristic of T cell exhaustion are present in sarcoidosis BAL.…”
Section: Resultsmentioning
confidence: 65%
“…We have shown that sarcoidosis CD4 + T cells derived from the periphery exhibit immune dysfunction when compared to healthy control cells (Figures 1 – 4 ). Together, these data reveal that the phenotypes observed in the periphery also occur at the site of local inflammation in the lung, a phenomenon also observed in sarcoidosis innate immune cells [ 33 ]. Thus, multiple immune defects characteristic of T cell exhaustion are present in sarcoidosis BAL.…”
Section: Resultsmentioning
confidence: 65%
“…Many of this module’s immunologic pathways have been implicated in the pathogenesis of sarcoidosis including aberrant T cell signaling, the IL17 pathway [ 22 ] as well as IL12, IL27, and IL23 family of cytokines [ 23 , 24 ]. Interestingly, natural killer (NK) cell cytotoxicity was also a member of this module, and deficiency in NK cell function has been linked to progression of sarcoidosis [ 25 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Cells were resuspended in 0.1% bovine serum albumin plus 2 mM ethylenediaminetetraacetic acid in phosphate-buffered saline (PBS) and immediately processed for flow cytometry. Peripheral blood mononuclear cells (PBMCs) were isolated as described previously (26).…”
Section: Bal and Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%